Incidence and prevalence of injuries in futsal: A systematic review of the literature - Gene-Morales, J.; Saez-Berlanga, Á.; Bermudez, M.; Flandez, J.; Fritz, N. B.; Colado, J. C. (Journal of Human Sport & Exercise, 2021)
Futsal athletes are exposed to a high number of injures. Purpose: This study aimed to gather data on the injures produced in futsal, attending to the prevalence, part of the body injured, type of injury and mechanism, and severity. Also, to evaluate the influence that sociodemographic factors and the position on the pitch may have on the injuries. Finally, we pursued to summarize the prevention strategies proposed by the expert literature. Design: Different search strategies were entered in PubMed, Scopus, Web of Science, and Sport Discuss databases. Results: 36 articles were selected to be reviewed. Futsal is situated among the sports with the highest injury incidence, being the main body part injured the lower limb, specifically the knees and ankles. Regarding the type of injury and the mechanism causing the injury, bone injuries are usually related to contact with rivals and muscle, tendon, and ligament injuries related to non-contact mechanisms. In this concern, non-contact injuries are frequently more severe than impact injuries. There is not a clear consensus on if more injuries occur in training or games, and on the severity of the major part of the injuries that occur in futsal. Concerning sex, male players seem to present a higher prevalence of ankle injuries while woman players present more incidence of knee sprains. The age was reported to be correlated with the incidence of injuries during futsal practice. No influence of the position on the field of play on the prevalence of injuries was observed in the literature. Some recommendations are gathered concerning the prevention of injuries. These recommendations are focused on player equipment, playing facilities, rules, physical assessment, and appropriate strength and conditioning preparation. Conclusion: The results presented in this study may help coaches and practitioners to understand crucial factors on the common injuries that occur in futsal. This may allow them to prevent potential injuries and maintain the athlete`s performance.